Cell-based therapies reverse the heart failure-altered right ventricular proteome towards a pre-disease state - Nour Makkaoui; Vidhya Prasad; Pritha Bagchi; Tiffany Carmona; Ke Li; Olivia L. Latham; Yuanyuan Zhang; Jingyun Lee; Cristina M. Furdui; Joshua T. Maxwell (Stem Cell Research & Therapy)
Abstract Background Congenital heart defects can lead to right ventricular (RV) pressure-overload and heart failure. Cell-based therapies, including mesenchymal stromal cells (MSCs) and c-kit positive cells (CPCs) have been studied clinically as options to restore heart function in disease states. Many studies have indicated these cells act through paracrine mechanisms to prevent apoptosis, promote cellular function, and regulate gene/protein expression. We aimed to determine the proteomic response of diseased hearts to cell therapy. Methods We utilized a juvenile rat model of RV pressure overload created by banding the pulmonary artery (PAB). Two weeks post-banding, bone marrow-derived mesenchymal stromal cells (MSCs) and 3 populations of CPCs (nCPCs, cCPCs, ES-CPCs) were delivered to the RV free wall. RV function and cellular retention were measured for four weeks post-injection, at which point hearts were extracted and the RV was excised for liquid chromatography and tandem mass spectrometry. Resulting RV proteomes were compared and analyzed using systems biology and bioinformatics. Results Proteomic profiling identified 1156 total proteins from the RV, of which 5.97% were significantly changed after PAB. This disease-altered proteome was responsive to cellular therapy, with 72% of the PAB-altered proteome being fully or partially reversed by MSC therapy. This was followed by nCPCs (54%), ES-CPCs (52%), and cCPCs (39%). Systems biology and bioinformatics analysis showed MSC, nCPC, or ES-CPC cell therapy is associated with a decrease in predicted adverse cardiac effects. We also observed an effect of cell therapy on the non-altered RV proteome, however, this was associated with minor predicted pathological endpoints. Conclusions Our data indicate MSCs, ES-CPCs, and nCPCs significantly reverse the PAB-altered proteome towards a pre-disease state in our animal model. These results indicate cell-based therapies show promise in improving RV function after pressure overload through partial restoration of the disease-altered cardiac proteome.